Estimates of effective guarantees and tax rates in the AFDC program for the post-OBRA period. - McKinnish, Terra; Sanders, Seth G.; Smith, Jeffrey (Journal of Human Resources)
We employ the model used by Fraker, Moffitt, and Wolf (1985) to estimate effective tax rates and guarantees in the Aid to Families with Dependent Children (AFDC) program for the years 1967–82 to produce comparable estimates for 1983–91. We compare this method of benefit prediction with other methods in the literature and clarify the interpretation of estimates generated using the Fraker, Moffitt, and Wolf model We use our estimates for the period from 1983 to 1991 to examine how effective AFDC tax rates and guarantee levels have changed over time and relative to nominal, or official, program parameters. Reprinted by permission of the publisher.